Camptothecin bioprocessing from Aspergillus terreus, an endophyte of Catharanthus roseus: antiproliferative activity, topoisomerase inhibition and cell cycle analysis - Ashraf S. A. El-Sayed; Abdelaleim I. ElSayed; Khalid M. Wadan; Sayed S. El-Saadany; Nouran A. A. Abd El-Hady (Microbial Cell Factories, 2024)
Abstract Attenuation of camptothecin (CPT) productivity by fungi with preservation and subculturing is the challenge that halts fungi to be an industrial platform of CPT production. Thus, screening for novel endophytic fungal isolates with metabolic stability for CPT production was the objective. Catharanthus roseus is one of the medicinal plants with diverse bioactive metabolites that could have a plethora of novel endophytes with unique metabolites. Among the endophytes of C. roseus, Aspergillus terreus EFBL-NV OR131583.1 had the most CPT producing potency (90.2 μg/l), the chemical identity of the putative CPT was verified by HPLC, FT-IR, NMR and LC–MS/MS. The putative A. terreus CPT had the same molecular mass (349 m/z), and molecular fragmentation patterns of the authentic one, as revealed from the MS/MS analyses. The purified CPT had a strong activity against MCF7 (5.27 μM) and UO-31 (2.2 μM), with a potential inhibition to Topo II (IC50 value 0.52 nM) than Topo 1 (IC50 value 6.9 nM). The CPT displayed a high wound healing activity to UO-31 cells, stopping their metastasis, matrix formation and cell immigration. The purified CPT had a potential inducing activity to the cellular apoptosis of UO-31 by ~ 17 folds, as well as, arresting their cellular division at the S-phase, compared to the control cells. Upon Plackett–Burman design, the yield of CPT by A. terreus was increased by ~ 2.6 folds, compared to control. The yield of CPT by A. terreus was sequentially suppressed with the fungal storage and subculturing, losing ~ 50% of their CPT productivity by 3rd month and 5th generation. However, the productivity of the attenuated A. terreus culture was completely restored by adding 1% surface sterilized leaves of C. roseus, and the CPT yield was increased over-the-first culture by ~ 3.2 folds (315.2 μg/l). The restoring of CPT productivity of A. terreus in response to indigenous microbiome of C. roseus, ensures the A. terreus-microbiome interactions, releasing a chemical signal that triggers the CPT productivity of A. terreus. This is the first reports exploring the potency of A. terreus, endophyte of C. roseus” to be a platform for industrial production of CPT, with an affordable sustainability with addition of C. roseus microbiome.